HUBUNGAN STRES TERHADAP GANGGUAN SIKLUS HAID DI MAS AL-KAUSAR AL-AKBAR - RAYCHAN FAHIRA; DWI MAYAHETI NASUTION (JURNAL ILMIAH KOHESI, 2021)
Stress is a body response that is not specific to the demands of the burden. During adolescence there are emotionalchanges that are not stable due to hormonal fluctuations during the menstrual cycle. Young women who experience irregularperiods can be caused by changes in hormone levels due to stress or are in an emotional state. This research method iscorrelative analytic with cross sectional design. The subjects of the study were 128 high school students of grade 1.2 and 3MAS Al-Kautsar Al-Akbar Medan who met the inclusion and exclusion criteria. The sampling technique uses total sampling.The majority of menstrual cycle disorders interrupted by the sample were abnormal (82.8%). The majority of stress samplesare moderate stress (32%). There is a significant correlation between stress and menstrual cycle disorders in MAS Al-KausarAl-Akbar (p = 0.002; r = 0.275).